2020
DOI: 10.1242/bio.052126
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids containing ether-bound hydrocarbon-chains are essential for efficient phagocytosis and neutral lipids of the ester-type perturb development in Dictyostelium

Abstract: Lipids are the building blocks for cellular membranes; they provide signalling molecules for membrane dynamics and serve as energy stores. One path of their synthesis is initiated by glycerol-3-phosphate acyltransferase (GPAT), which in Dictyostelium resides on the endoplasmic reticulum. When an excess of fatty acids is present, it redistributes to storage organelles, the lipid droplets. Mutants, where the GPAT was eliminated by homologous recombination, produce fewer lipid droplets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
2
3
0
Order By: Relevance
“…Our untargeted LC-MS/MS lipidome analyses revealed that, in line with previous studies (27,60), the phospholipid pool in D. discoideum is mostly composed of ether lipids, i.e. lipids with ether-linked acyl-chains that are less abundant in mammals (75,76) and absent in plants or fungi (77).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our untargeted LC-MS/MS lipidome analyses revealed that, in line with previous studies (27,60), the phospholipid pool in D. discoideum is mostly composed of ether lipids, i.e. lipids with ether-linked acyl-chains that are less abundant in mammals (75,76) and absent in plants or fungi (77).…”
Section: Discussionsupporting
confidence: 88%
“…2A, Supplemental Table 2). These data are consistent with those reported previously by others (27,60,61). Besides, diacylphospholipids (~ 88.7 mol %), D. discoideum contains substantial amounts of lysophospholipids (~ 6.8 mol %), notably lysophosphatidyl-ethanolamine (LPE), Cers (~ 0.6 mol %), diacylglycerol (DAG, ~ 2.3 mol %) and triacylglycerols (TAG; ~ 1.6 mol %) (Fig.…”
Section: Phosphatidylethanolamine Is the Most Abundant Phospholipid I...supporting
confidence: 92%
See 1 more Smart Citation
“…Besides, GPAT4-deficient mice lack breast milk, making it difficult for pups to survive unless they are replaced or the adoptive mother is changed (Ref. 59). Information about different GPAT subtypes is still limited, and not yet fully understood, so further research is necessary to better understand the physiological and pathological effects of GPAT subtypes.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Examples include etheric membrane lipids from Archaea, [2] ladderane membrane lipids from anaerobic ammonia-oxidizing (anammox) bacteria, [3] paramecyl alcohol from ciliate Paramecium tetraurelia, [4] diacylglyceryl ether from marine animals, [5] betaine lipids from micro-and macroorganisms except seed-bearing plants or metazoans, [6] plasmalogens, [7] seminolipids, [8] and platelet-activating factor [9] from mammals (Figure 1). The physiological roles of these molecules are yet fully understood, but some are known to be associated with the ability to adapt to extreme environments such as high temperature, low pH, high salinity, [10] and phosphorous deprivation, [11,12] or a variety of biological events including ATP synthesis, [13] establishment of infection, [14] phagocytosis, [15] to acquire buoyance in the deep sea, [16][17][18] spermatogenesis, [19] immunity, [7] neuronal development, [7] lens organization, lens transparency, [20] and for radical scavenging. [7] In mammals, deficiencies in ether lipid biosynthesis cause two serious congenital disorders, rhizomelic chondrodysplasia punctata (RCDP) and Zellweger spectrum disorders, and lower ether lipid levels in serum or tissues are associated with a range of neurological and metabolic diseases [21] including Alzheimer's disease (AD), schizophrenia, Parkinson's disease (PD), Down syndrome, Gaucher disease, Niemann-Pick type C disease, diabetes, cardiovascular disease, and cancer.…”
Section: Introductionmentioning
confidence: 99%